Peningkatan Hasil Belajar Matematika Siswa Kelas III SD IT Nur Ihsan Medan melalui Pendekatan Pembelajaran Kontekstual - Rizka Hidayah husin Lubis (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose of this study was to improve students' mathematics learning outcomes by using a Contextual Approach in class III SD IT Nur Ihsan Medan. This type of research is classroom action research. The application of a contextual learning approach in improving mathematics learning outcomes in multiplication and division arithmetic operations material in class III SD IT Nur Ihsan is carried out with the following steps: (1) Relating, (2) Experiencing, (3) Cooperating (4) Applying, (5) Transfers. The application of a contextual learning approach can improve learning outcomes in mathematics subjects, multiplication and division operations for class III SD IT Nur Ihsan. This can be seen from the average initial condition before the research was carried out, which was 64.51 with a completeness percentage of 44.44%. After doing research in the first cycle using a contextual learning approach on the material of multiplication and division arithmetic operations has increased with an average value of 76.53 with the percentage of students' completeness reaching 73.33%. Then proceed to cycle II by applying a contextual learning approach, student learning outcomes have increased. In the second cycle the average increased to 87.2 with the percentage of students' completeness reaching 86.66%.